Prevalence of Extended Spectrum b-Lactamases (ESBLs) Producers Among Gram-Negative Bacilli in Urinary Tract Infections (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Antimicrobial resistance is now proclaimed as the most important challenge worldwide being faced by humanity in its fight against infectious diseases. Extended Spectrum b-Lactamases (ESBLs) producing organisms are increasing in number and causing more severe infections because of their continuous mutation and multidrug resistance property which make its treatment difficult.Aims: The present study was undertaken to detect the prevalence of the ESBLs producing bacteria in urinary tract infection.Methods: Isolated gram-negative bacteria initially screened by Minimum Inhibitory Concentration (MIC) ESBLs breakpoints. Then suspected ESBLs producers were confirmed by phenotypic confirmatory test.Results: 71 (59.17%) bacterial strains were isolated from 120 urine samples of patients of suspected urinary tract infection of which 66(92.96%) were gram-negative and 05(07.04%) were gram-positive. Among the isolated gram-negative bacteria 63(95.45%) were found suspected ESBLs producers of which 35(55.56%) were found as confirmed ESBL producers. The prevalence of ESBLs producing organisms in the present study were found to be 53.03% and Klebsiella spp. as most prevalent ESBLs producers.Conclusion: It is essential to report ESBL production along with routine sensitivity reporting, which will help the clinician in prescribing the proper antibiotics.Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 17-20